Mahmudah, S SPIRITUAL LEADERSHIP PADA KONTEKS PERBANKAN SYARIAH: STUDI VALIDITAS DAN RELIABILITAS KONSTRUK (Nsc Press, 2017)
The goals of this study are to describe the spiritual leadership at sharia banking context, to analysis the construct validity and reliability of the spiritual leadership, and to find the indicators forming the construct of spiritual leadership. Spiritual leadership was measured with four indicators: vision, faith, altruistic love and inner life. Explanatory with descriptive and inferential analysis was used. Inferential analysis is performed using Structural Equation Modeling (SEM) AMOS and SPSS program version 19. Data were taken from 288 employees of Islamic rural bank in East Java by questionnaire who had been used area proportional random sampling techniques. Questionnaires were filled with a total of 288 respondents and feasible to analyse were 287 respondents (response rate 99.31%). The results showed that spiritual leadership of individual employee at Islamic rural bank in East Java is good; all items questions are valid and forth dimensions are reliable; spiritual leadership had good construct validity and reliability; and the fourth indicators of spiritual leadership has a t-value significant standardized loading factor as forming the construct of spiritual leadership. The dominant dimension influencing the spiritual leadership construct was faith.